Oxidative stress strongly restricts the effect of codon choice on the efficiency of protein synthesis in Escherichia coli - Leiva, Lorenzo Eugenio; Elgamal, Sara; Leidel, Sebastian A.; Orellana, Omar; Ibba, Michael; Katz, Assaf (Frontiers in Microbiology, 2022)
The response of enterobacteria to oxidative stress is usually considered to be regulated by transcription factors such as OxyR and SoxR. Nevertheless, several reports have shown that under oxidative stress the levels, modification and aminoacylation of tRNAs may be altered suggesting a role of codon bias in regulation of gene expression under this condition. In order to characterize the effects of oxidative stress on translation elongation we constructed a library of 61 plasmids, each coding for the green fluorescent protein (GFP) translationally fused to a different set of four identical codons. Using these reporters, we observed that GFP production levels vary widely (~15 fold) when Escherichia coli K-12 is cultured in minimal media as a consequence of codon choice variations. When bacteria are cultured under oxidative stress caused by paraquat the levels of GFP produced by most clones is reduced and, in contrast to control conditions, the range of GFP levels is restricted to a ~2 fold range. Restricting elongation of particular sequences does not increase the range of GFP production under oxidative stress, but altering translation initiation rates leads to an increase in this range. Altogether, our results suggest that under normal conditions the speed of translation elongation is in the range of the speed of initiation and, consequently, codon choice impacts the speed of protein synthesis. In contrast, under oxidative stress translation initiation becomes much slower than elongation, limiting the speed of translation such that codon choice has at most only subtle effects on the overall output of translation.